The public intellectual in Canada - Wiseman, Nelson, 1946- (2013)
"The all-star cast of contributors in this collection is a truly impressive assembly. Many are widely know and will be familiar to the reader. All of them have influenced public affairs in Canada as doers as well as thinkers and they span the ideological spectrum. With them, we explore and examine the place of the public intellectual in the context of a rapidly changing and diverse Canadian society in an increasingly interdependent world. Contributors: Michael Adams, Maude Barlow, Sylvia Bashevkin, Gregory Baum, Stephen Clarkson, Tom Flanagan, Pierre Fortin, Alain-G. Gagnon, Mark Kingwell, John Richards, Doug Saunders, Hugh Segal, Margaret Somerville, Janice Gross Stein, Nelson Wiseman."--page 4 of cover
Keywords: Intellectuals -- Canada; Intellectuels -- Canada; Canada -- Intellectual life; Canada -- Vie intellectuelle